Statement of Support for Democratically Elected School Boards / Déclaration à l'appui des commissions scolaires démocratique élues - APPELE-Québec (2023)
Keywords: Official Language Minority Community (OLMC)

APPELE-Québec critique vivement le gouvernement du Québec pour son changement d'avis sur les élections dans lescommissions scolaires anglophones - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

APPELE-Québec Slams Quebec Government for Flip Flop on School Board Elections - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

Court Challenge to Bill 40 Launched : Qubec's English-Speaking Minority Seeks Interlocutory Injunction - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

English-speaking Community Challenges the Constitutionality of Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

APPELE-Québec Deplores Government Haste in Involving Closure on Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

APPELE-Québec Disappointed with Government's Hasty Decision to Reject Court Reference - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

APPELE-Québec Proposes Path for Breaking Impasse on Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

Compte rendu des audiences publiques sur le projet de loi no 40 tenues par APPELE-Québec - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)
APPELE-Québec a entendu 18 groupes et particuliers lors des audiences publiques qu’il a commanditées, portant sur le projet de loi no 40 : Loi modifiant principalement la Loi sur l’instruction publique relativement à l’organisation et à la gouvernance scolaires. Lors de cet exercice, nous avons pu entendre le point de vue d’un vaste échantillon de représentants de la communauté anglophone du Québec ainsi que des parties concernées originaires de l’ensemble du Canada.

Report on Hearings on Bill 40 Organized by APPELE-Québec - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)
APPELE-Québec heard from 18 groups and individuals at hearings it sponsored on Bill 40; An Act to amend mainly the Education Act with regard to school organization and governance. We benefited from the input of a wide cross-section of representatives from Quebec’s English-speaking community as well as from concerned parties from across Canada.

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

Bill 40 Submission by APPELE-Québec - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)

Mémoire présenté sur le projet de loi 40 par APPELE-Québec - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)

Brief to Appele Quebec on Bill 40 : an Act to Amend Mainly the Education Act with Regard to School Organization and Governance - Buck, John (Community Economic Development and Employability Corporation (CEDEC), 2019)
The Community Economic Development and Employability Corporation, CEDEC, has been intimately involved over the last twenty-five years in developing and enhancing the vitality of the English-speaking Minority Community of Quebec. CEDEC is committed to improving the economic well-being of communities. It is a hub of innovative research and practice focused on enhancing economic activity that benefits communities through public, private, and civil society collaboration.

Community Unites to Fight for Domocratically Elected School Boards - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)